RECALL ASWANTO: TERTUTUPNYA RUANG DISAGREEMENT ANTARA PEMBENTUK UNDANG-UNDANG DAN MAHKAMAH KONSTITUSI - Kurnia, Titon Slamet (Universitas Kristen Satya Wacana, 2023)
This article discusses the recall directed to Justice Aswanto of the Constitutional Court during his tenure by the House of Representatives (DPR). The DPR recalls Justice Aswanto due to its disagreement with his judicial performance. According to the law, the Constitutional Court Justices may only be removed from office during his/her tenure through the Ethical Council of the Constitutional Court. This article argues that the recall is inconsistent with the principle of security of tenure and, therefore, contradicts the principle of judicial independence. Unfortunately, this issue is not the main problem. The primary issue is that the legislature has no room to disagree with the Constitutional Court's interpretation in reviewing the constitutionality of legislation. This issue arises because the Constitution, UUD 1945, allocates the finality of the constitutional review mechanism in the judiciary. In solving the issue, this article refers to the Canadian model of constitutional review. The concept of the Canadian model is a judicial review with legislative finality.